A SUFISM PSYCHOLOGICAL ANALYSIS OF ISMᾹ’ÎL’S INTRAPERSONAL COMMUNICATION IN SURAH AL-SᾹFFᾹT [37]: 102 - Mahbub Ghozali (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2020)
Dialogue between Ismā’îl and Ibrāhîm in Q.S. al-S{affāt [37]: 102, is not only focused on the polemic of the determination about child referred in the verse. Likewise, the discussion about this verse is not only abaout ideal model of education for children. Another discussion no less interesting is regarding the response of the Ismā'îl when listening to the slaughtering order from Ibra>hi>m. Although there is no indication in the verse that reffer to communicative process in Ismā'îl to response that command. But in the context of communication, the reception of the message conveyed, allows him to respond the message. To provide a response, symbol processing is needed. So that it can provide an appropriate response. Therefore, to find this process, this study uses a text analysis method with a Sufi Psychological approach. By using these methods and approaches, this study concludes that intrapersonal communication in Ismā’îl involves self-entities consisting of al-rûh}, al-‘aql, and al-qalb. These three entities have their respective concepts of knowledge which clarify one another. In Ismā’îl, the concept of reason knowledge gained from his experiences gives confidence to the truth of the command. Likewise, the maturity of the soul makes it easy for the heart to gain intuitive knowledge that is affirmed by reason, giving rise to an acceptance response to the order.